Evaluation of the content of ceruloplasmin, copper and coppercoordinating amino acids in cow milk at different lactation periods - O. A. Voronina; S. Yu. Zaitsev; A. A. Savina; N. S. Kolesnik (Аграрная наука Евро-Северо-Востока, 2023)
The purpose of the research was to study the content of ceruloplasmin, copper and copper-coordinating amino acids (in the molecule of the studied protein) in the milk of white-and- black cows at different periods of lactation. The research methods were: modified method for determining ceruloplasmin by Revin; copper was determined using a ZEEnit 650 P atomic adsorption spectrometer (Analytik Jena AG, Germany), amino acid analysis was performed using a highly efficient LC-20 Prominence liquid chromatography system (Shimadzu, Tokyo, Japan) equipped with a reaction module for post-column derivatization with ninhydrin ARM-1000 (Sevko & Co., Moscow, Russia). The study groups were formed depending on the timing of lactation: 1-2 months – group 1; 3-5 months – group 2; 6-7 months – group 3; 8-9 months – group 4. Each group included 8 animals. The Mann-Whitney U criterion and Pearson correlations were used for statistical processing of the obtained results. The average values of ceruloplasmin levels in the groups were 0.44-0.49 mg/ml, copper 71-83 mcg/l, histidine 0.11-013 g/100g, cysteine 0.03 g/100g and methionine 0.09-0.11 g/100g. In these 4 groups, small differences were found in the content of ceruloplasmin, copper and three amino acids, but only for the second and fourth groups of histidine, these differences were significant. Thus, the indicated intervals of ceruloplasmin and copper content can serve as important guidelines for determining the "reference intervals" for cow milk in general, while it is not necessary to take into account different lactation periods.